The effect of musical tempo on video game performance - Lawrence, Daniel (2012)
There is little research on music and audio in video games. What theory exists relies heavily upon borrowing concepts from similar fields such as film music. The empirical research conducted has been varied in scope, but small in number. This thesis explores the current state of theory and research in video game music and audio. In order to investigate if music can affect performance in a video game, an experiment was conducted. Participants were asked to play the popular video game Tetris multiple times to music of varying tempi. The performance of each participant for every game played was recorded and compared across the conditions. Although no statistically significant differences in performance were observed between the tempi, this study sets a framework for future experiments in the same field.